IMPLEMENTATION OF RICHARD C. MARTIN'S THOUGHT IN MODERN ISLAMIC STUDIES 5.0 (Approaches to Islamic Religious Studies) - Akmal Ihsan; Sulaiman Sulaiman; Syafira Anisatul Izah; Alan Budi Kusuma (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This paper examines Richard C. Martin's Islamic studies in the book Approaches to Islam in Religious Studies on modern Islamic studies 5.0. This study is an analytical descriptive form that begins by revealing the author's background to how the Islamic studies approach is offered. Starting with Martin's thoughts, he saw that western scholars, especially those in North America, failed to understand modern Islamic studies 5.0, this was based on the weak theological approach that maintained a normative understanding of religion and the historical point of view that cornered Islam as a result of the Islamic-Christian wars in the Middle Ages. In this study, it puts forward approaches as a reference for the study of the modern Islamic religion. For this reason, Martin tries to provide an understanding through this book with several approaches that are believed to have a major influence in the 20th century on modern Islamic studies, especially in the 5.0 generation. The approach in question is scripture and prophet; rituals and community; religion and society; scholarship and interpretation, and challenge and criticism. Where this approach is able to uncover and analyze dynamic Islamic studies following contemporary times, as well as being able to locate the weaknesses in modern Islamic studies